The effects of breeding protocol in C57BL/6J mice on adult offspring behaviour. - Claire J Foldi; Darryl W Eyles; John J McGrath; Thomas H J Burne (PLoS ONE, 2011)
Animal experiments have demonstrated that a wide range of prenatal exposures can impact on the behaviour of the offspring. However, there is a lack of evidence as to whether the duration of sire exposure could affect such outcomes. We compared two widely used methods for breeding offspring for behavioural studies. The first involved housing male and female C57Bl/6J mice together for a period of time (usually 10-12 days) and checking for pregnancy by the presence of a distended abdomen (Pair-housed; PH). The second involved daily introduction of female breeders to the male homecage followed by daily checks for pregnancy by the presence of vaginal plugs (Time-mated; TM). Male and female offspring were tested at 10 weeks of age on a behavioural test battery including the elevated plus-maze, hole board, light/dark emergence, forced swim test, novelty-suppressed feeding, active avoidance and extinction, tests for nociception and for prepulse inhibition (PPI) of the acoustic startle response. We found that length of sire exposure (LSE) had no significant effects on offspring behaviour, suggesting that the two breeding protocols do not differentially affect the behavioural outcomes of interest. The absence of LSE effects on the selected variables examined does not detract from the relevance of this study. Information regarding the potential influences of breeding protocol is not only absent from the literature, but also likely to be of particular interest to researchers studying the influence of prenatal manipulations on adult behaviour.